TFF3 interacts with LINGO2 to regulate EGFR activation for protection against colitis and gastrointestinal helminths - Nicole Maloney Belle (Nature Portfolio, 2019)
TFF3 secretion by goblet cells regulates mucus viscosity and wound healing, but a receptor for TFF3 has not been identified. Here, the authors show that TFF3 binds LINGO2 to de-repress and enhance EGFR signaling that drives wound healing and immunity against helminths.